A Pragmatic Inquiry into Employee's Lived Experiences in relation to COVID-19 Lockdown in South Africa - Costa, King; Tumagole, Benevolent (My University, 2020)
The outbreak of COVID-19 in South Africa has brought about many socio-economic challenges, affecting everyone in all sectors of society. As the government proactively introduced steps to deal with the progression of the COVID-19 in South Africa, some of these measures included a total country lock-down, introduced on the 26th of March 2020. One of the most severely impacted sectors of society was employees from different organizations. Such impacts included confusion, fear of contracting the virus, and mixed emotions in relation to their income including survival of their organizations during the lockdown. This study used a mixed-methods approach to understand employees’ experiences during the period of lockdown in South Africa. The study design used a pragmatic approach, employing an explorative inductive sequential logical approach whereby phenomenology was used as a method of inquiry, followed by survey research which was constructed out of data from the qualitative dimension of the study. Findings from the qualitative study were triangulated with findings from the quantitative dimension. Results from both dimensions seemed very plausibly similar, indicating the need for attention of employee’s mental health emanating from COVID-19 phenomena and subsequent lockdown in South Africa. Provision of safe working environments, the establishment of peer educators, strengthening of Employee Assistance Programme (EAP) services, and corporate health initiatives by employers were recommended as proactive initiatives to assist and enhance the wellbeing of employees during and post COVID-19.
Keywords: COVID-19; Employees; Lived experiences; Fear of coronavirus; South Africa; Workplace safety; Lack of support; Company response